POLITIK LUAR NEGERI CHINA TERHADAP ZIMBABWE - Nurdiani Fathiraini (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This article aimed to elaborate China’s foreign policy towards Zimbabwe under Hu Jintao’s leadership. Based on the “social construction” logic, it was a logical consequence influenced by intersubjective factors and also formed and defined based on the actor’s social identity. In this case, historical power influenced a positive intersubjective and form an established structure of China “amity” towards Zimbabwe. It can be understood how China perceived Zimbabwe as a “friend”. Besides, China’s identity transformation as a “peaceful rise” country, defined the interest formation towards economic and development cooperation manifested through strengthening cooperation in the China-Zimbabwe Strategic Partnership’s scheme. Thus, Hu Jintaos foreign policy towardsZimbabwe was not only determined by the material dimension, but strongly determinedby the ideational dimension where China under Hu Jintao’s leadership was strivedto represent of a “peaceful rise” identity that cannot be separated from the values of“friendship, peace, cooperation, and development.